2010
DOI: 10.1002/rem.20262
|View full text |Cite
|
Sign up to set email alerts
|

Electrical resistance heating of volatile organic compounds in Sedimentary rock

Abstract: Electrical resistance heating (ERH) has become a common method of remediation for volatile or-ganic compounds (VOCs) ELECTRICAL RESISTANCE HEATING PROCESSElectrical resistance heating (ERH) passes an electrical current through the soil, rock, and groundwater that requires treatment. The principal current path is the thin layer of water immediately adjacent to the soil or rock grains-relatively little current is carried by the water in the soil pores. The electrical current warms the subsurface and then boil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…After operating for 148 d, the average temperature reached 100 °C and the TCE concentrations were reduced up to 99.7% within the treatment zone (Heron et al ). Kluger and Beyke () showed that the same heating rate was achieved for the cemented sandstone layer and the soil layer at a site in Annapolis, Indiana, using ERH method. They also reported remediation of a fractured limestone bedrock contaminated with CVOCs (TCE is the dominant contaminant) using ERH method at a site in Greensburg, Indiana (Kluger and Beyke ).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…After operating for 148 d, the average temperature reached 100 °C and the TCE concentrations were reduced up to 99.7% within the treatment zone (Heron et al ). Kluger and Beyke () showed that the same heating rate was achieved for the cemented sandstone layer and the soil layer at a site in Annapolis, Indiana, using ERH method. They also reported remediation of a fractured limestone bedrock contaminated with CVOCs (TCE is the dominant contaminant) using ERH method at a site in Greensburg, Indiana (Kluger and Beyke ).…”
Section: Introductionmentioning
confidence: 83%
“…Kluger and Beyke () showed that the same heating rate was achieved for the cemented sandstone layer and the soil layer at a site in Annapolis, Indiana, using ERH method. They also reported remediation of a fractured limestone bedrock contaminated with CVOCs (TCE is the dominant contaminant) using ERH method at a site in Greensburg, Indiana (Kluger and Beyke ). After more than 5 months of operation, the CVOC concentrations at the site were decreased by 95% (Kluger and Beyke ).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Recently, ERH has been used to treat contaminated sedimentary bedrocks, and fi eld trials were held in Maryland, New Jersey and Indiana (Kluger and Beykle 2010 ). In 2006, at Annaolis, Maryland, tetrachloroethylene (TCE) contamination was observed extensively in surface soils.…”
Section: Electrical Resistance Heatingmentioning
confidence: 99%
“…Operators use temperature measurements to monitor ERH progress (Kluger and Beyke ), and it has been shown that temperature plateaus are indicative of co‐boiling at a NAPL–water interface. Temperature plateaus have been observed in homogeneous media (DeVoe and Udell ; Burghardt and Kueper ; Hegele and Mumford ; Zhao et al ), and media with moderate permeability contrasts (Martin and Kueper ).…”
Section: Introductionmentioning
confidence: 99%